Robust Spoken Language Understanding in MiPad - Wang, Ye-Yi (Eurospeech, 2001)
MiPad is an application prototype for the study of conversational, multi-modal interface in Microsoft Research. It has a Tap and Talk interface that allows users to effectively interact with a PDA device. The major Spoken Language Understanding (SLU) engine component behind MiPad is a robust chart parser. This paper discusses some novel features of the parser that enable it to take full advantage of the Tap and Talk interface and better support semantic based analysis. It also describes some implementation issues so that these new features can be accommodated without slowing down the parser. The new implementation speeds up the parser by a factor of three, making it more suitable for a SLU server.